2021
DOI: 10.3390/molecules26061562
|View full text |Cite
|
Sign up to set email alerts
|

Novel Multifunctional Ascorbic Triazole Derivatives for Amyloidogenic Pathway Inhibition, Anti-Inflammation, and Neuroprotection

Abstract: Alzheimer’s disease (AD) is a common neurodegenerative disorder. The number of patients with AD is projected to reach 152 million by 2050. Donepezil, rivastigmine, galantamine, and memantine are the only four drugs currently approved by the United States Food and Drug Administration for AD treatment. However, these drugs can only alleviate AD symptoms. Thus, this research focuses on the discovery of novel lead compounds that possess multitarget regulation of AD etiopathology relating to amyloid cascade. The as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 64 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…According to the data from International Dementia Association, there are more than 50 million people with dementia worldwide, and the total number of people with dementia is predicted to reach 152 million in 2050, with one patient almost every 3 s. [1,2] Alzheimer's disease (AD) is currently the DOI: 10.1002/mnfr.202200265 most widespread and afflicted dementia in the world. [3] The pathogenesis of AD is very complex and has not yet been fully resolved, there are multiple pathogenic hypotheses, such as the amyloid cascade, [4] abnormal phosphorylation of tau protein, [5] cholinergic, [6] neuroinflammation, [7] mitochondrial dysfunction, [8] etc.…”
Section: Introductionmentioning
confidence: 99%
“…According to the data from International Dementia Association, there are more than 50 million people with dementia worldwide, and the total number of people with dementia is predicted to reach 152 million in 2050, with one patient almost every 3 s. [1,2] Alzheimer's disease (AD) is currently the DOI: 10.1002/mnfr.202200265 most widespread and afflicted dementia in the world. [3] The pathogenesis of AD is very complex and has not yet been fully resolved, there are multiple pathogenic hypotheses, such as the amyloid cascade, [4] abnormal phosphorylation of tau protein, [5] cholinergic, [6] neuroinflammation, [7] mitochondrial dysfunction, [8] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, compound 37 was the most potent inhibitor with IC 50 value of 92.33 μM (Figure ). Structure–activity relationship indicated that substitution of tryptoline next to triazole ring was more preferable than phenol or 2-methoxy phenol . In order to optimize the above studies, Jiaranaikulwanitch et al replaced the tryptoline with tryptamine, and on the other side ascorbic acid was replaced with the metal chelator aromatic ring based on the structural features reported by the Reinke and Gestwicki .…”
Section: 23-triazole Containing Derivatives For Development Of Anti-a...mentioning
confidence: 99%
“…Structure− activity relationship indicated that substitution of tryptoline next to triazole ring was more preferable than phenol or 2methoxy phenol. 155 In order to optimize the above studies, Jiaranaikulwanitch et al replaced the tryptoline with trypt- amine, and on the other side ascorbic acid was replaced with the metal chelator aromatic ring based on the structural features reported by the Reinke and Gestwicki. 156 The series of tryptamine triazole derivatives was synthesized and evaluated as amyloid-β aggregation inhibitors.…”
Section: 23-triazole Containing Derivatives Inspired From Clinically ...mentioning
confidence: 99%
“…Alzheimer’s disease (AD) is a common neurodegenerative disorder found in elderly people 1 . This disease is a common form of dementia, including loss of memory and cognitive function impairments 2 , 3 . The etiology of AD is unknown.…”
Section: Introductionmentioning
confidence: 99%